Pharmacokinetic and Pharmacodynamic Evaluation of Marbofloxacin and PK/PD Modeling against Escherichia coli in Pigs - Lei, Zhixin; Liu, Qianying; Xiong, Jincheng; Yang, Bing; Yang, Shuaike; Zhu, Qianqian; Li, Kun; Zhang, Shishuo; Cao, Jiyue; He, Qigai (Frontiers in Pharmacology, 2017)
The aim of this study was to evaluate the activity of marbofloxacin and establish the optimal dose regimens for decreasing the development of fluoroquinolone resistance in pigs against Escherichia coli with ex vivo pharmacokinetic/pharmacodynamic (PK/PD) modelling. The recommended dose (2 mg/kg body weight) of marbofloxacin was orally administered in healthy pigs. The ileum content and plasma were both collected for the determination of marbofloxacin. The main parameters of Cmax, AUC0-24h, AUC, Ke, t1/2ke, MRT and Clb were 11.28 μg/g, 46.15, 77.81 μg•h/g, 0.001 h-1, 69.97 h, 52.45 h, 0.026 kg/h in ileum content, and 0.55 μg/ml, 8.15, 14.67 μg•h/ml, 0.023 h-1, 30.67 h, 34.83 h, 0.14 L/h in plasma, respectively In total, 218 Escherichia coli strains were isolated from most cities of China. The antibacterial activity in vitro and ex vivo of marbofloxacin against Escherichia coli was determined following CLSI guidance. The MIC90 of sensitive strains (142) was calculated as 2 μg/ml. The minimum inhibitory concentration (MIC) of HB197 was 2 and 4 μg/ml in broth and ileum fluids, respectively. In vitro mutant prevention concentration (MPC), growth and killing-time in vitro and ex vivo of marbofloxacin against selected HB197 were assayed for pharmacodynamic studies. According to the inhibitory sigmoid Emax modelling, the value of AUC0-24h/MIC produced in ileum content was achieved, and bacteriostatic, bactericidal activity, and elimination were calculated as 16.26, 23.54 and 27.18 h, respectively. Based on Monte Carlo simulations to obtain 90% target attainment rate, the optimal doses to achieve bacteriostatic, bactericidal and elimination effects were 0.85, 1.22 and 1.41 mg/kg.bw for 50% target, respectively, and 0.92, 1.33 and 1.53 mg/kg.bw for 90% target, respectively, after oral administration. The results in this study provided a more optimised alternative for clinical use and demonstrated that the dosage 2 mg/kg of marbofloxacin by oral administration could have an effect on bactericidal activity against E. coli.